Real‐time detection of N‐end rule‐mediated ubiquitination via fluorescently labeled substrate probes1. Issue 2 (9th March 2017) - Mot, Augustin C.; Prell, Erik; Klecker, Maria; Naumann, Christin; Faden, Frederik; Westermann, Bernhard; Dissmeyer, Nico
Summary: The N‐end rule pathway has emerged as a major system for regulating protein functions by controlling their turnover in medical, animal and plant sciences as well as agriculture. Although novel functions and enzymes of the pathway have been discovered, the ubiquitination mechanism and substrate specificity of N‐end rule pathway E3 ubiquitin ligases have remained elusive. Taking the first discovered bona fide plant N‐end rule E3 ligase PROTEOLYSIS1 (PRT1) as a model, we used a novel tool to molecularly characterize polyubiquitination live, in real time. We gained mechanistic insights into PRT1 substrate preference and activation by monitoring live ubiquitination using a fluorescent chemical probe coupled to artificial substrate reporters. Ubiquitination was measured by rapid in‐gel fluorescence scanning as well as in real time by fluorescence polarization. The enzymatic activity, substrate specificity, mechanisms and reaction optimization of PRT1‐mediated ubiquitination were investigated ad hoc instantaneously and with significantly reduced reagent consumption. We demonstrated that PRT1 is indeed an E3 ligase, which has been hypothesized for over two decades. These results demonstrate that PRT1 has the potential to be involved in polyubiquitination of various substrates and therefore pave the way to understanding recently discovered phenotypes of prt1 mutants.